UJI DAYA TERIMA DAN KANDUNGAN GIZI NASI DENGAN PENAMBAHAN LABU KUNING DAN JAGUNG MANIS - Hadiah Kurnia Putri; Jumirah .; Zulhaida Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Food diversification instead of rice is necessary for food security and food quality. Pumpkin and sweet corn can be an alternative to accompanying rice for the food security and food quality. This was an experimental study on rice processing by adding pumpkin and sweet corn in different proportion (5:3:2, 5:2:3, and 5:2,5:2,5). This study was aimed to determine the acceptability of color, flavor, taste, and texture which were tested by hedonic test and its nutrient composition. The result of this research showed that by organoleptic test, rice with the addition of pumpkin and sweet corn which made with 5:3:2 proportion was the most favored by the panelists. Based on analysis of variance, the addition of pumpkin and sweet corn in different proportion influenced different variety of taste, flavor, color, and texture. The addition of pumpkin and sweet corn on rice cooking increased the content of protein, fat, calcium, phosphorus, iron, vitamin A, vitamin B1, and vitamin C. Consumption of one serving of A1 rice with addition pumpkin and sweet corn contributes 26,8% adequacy of vitamin A and 40,0% adequacy of vitamin C in 7-9 years old children. It is suggested for consumer to make rice with addition of pumpkin and sweet corn as an alternative food for reduce the consumption of rice. It is necessary to do other foods diversification by added pumpkin and sweet corn as a food which is rich in nutrient content. Keywords: Rice, Pumpkin, Sweet Corn, Acceptability Test, Nutrient Composition